2016
DOI: 10.1111/jog.12965
|View full text |Cite
|
Sign up to set email alerts
|

Tardive intermittent massive vaginal bleeding from abnormal blood vessels within cesarean scar: Two more new cases should bring our attention to a new entity

Abstract: The two cases in this report had intermittent massive vaginal bleeding with a distant history of cesarean delivery. Such severe bleeding was life-threating but was eventually cured by surgical management. To the best of our knowledge, this is the second report of cases of tardive vaginal bleeding caused by abnormal blood vessels embedded within cesarean scars. The two new cases in this report suggest a novel cause of tardive vaginal bleeding, which should bring our special attention to post-cesarean clinical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…also reported two cases of tardive vaginal bleeding caused by rupture of abnormal blood vessels within the cesarean scar diagnosed by hysteroscopy. [5] These cases showed massive hemorrhage and needed blood transfusion and surgical repair as with our case. Such life-threatening hemorrhage from cesarean scar was previously reported only in these two reports and might be very rare condition.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…also reported two cases of tardive vaginal bleeding caused by rupture of abnormal blood vessels within the cesarean scar diagnosed by hysteroscopy. [5] These cases showed massive hemorrhage and needed blood transfusion and surgical repair as with our case. Such life-threatening hemorrhage from cesarean scar was previously reported only in these two reports and might be very rare condition.…”
Section: Discussionmentioning
confidence: 54%
“…Massive bleeding such as that in the present case is extremely rare. [56] We report the clinical course and details of the laparoscopic treatment in this case.…”
Section: Introductionmentioning
confidence: 99%
“…The scar tissue generated by isthmocele can create an indentation in the uterine wall, where menstrual blood can accumulate. This can prevent blood from being expelled regularly during menstrual flow, causing intermittent blood loss [59]. Additionally, scar tissue can interfere with the normal contraction of the uterus during the menstrual cycle.…”
Section: Intermittent Spottingmentioning
confidence: 99%
“…If the sac (star) is embedded in the hysterotomy scar or thrombus/fibrous tissues, this may prevent physicians from recognizing the sac itself, and thus, UAP. One may consider that bleeding occurred from abnormal vessels present in the CS scar, as in the cases that Liao et al 1 described.…”
mentioning
confidence: 99%
“…Taking (i)-(v) into consideration, one may not recognize the presence of UAP, and may consider that bleeding has occurred from the artery itself; this may be especially true if one is not suspicious of the presence of UAP. Liao et al 1 claimed that their cases revealed 'a new entity' based on three characteristics; however, these same features are characteristic of UAP: (i) repeated and intermittent bleeding; (ii) its presence around the CS scar; and (iii) rupture long after CS. In fact, detection of an internal iliac artery pseudoaneurysm 20 years after CS has been reported.…”
mentioning
confidence: 99%